The modern seed-fertiliser technology and adoption of labour-saving technologies - the philippine case - David, Cristina C.; Otsuka, Keijiro (Wiley, 1990)
While intervillage differences in the adoption of modern rice varieties (MVs) are explained mainly by environmental variables, rather than by socioeconomic factors, relative factor prices are the most important determinants of the adoption oflabour‐saving technologies. There is no indication that MV adoption is correlated with the adoption of tractors and threshers as well as cropping intensities. Adoption of direct seeding, however, appears to be associated with MV adoption.